Cross-cultural responsiveness and cross-national approaches in offender rehabilitation: research and practice considerations - Tamatea, Armon J. (Approaches to offender rehabilitation in Asian jurisdictions, 2024)
Offending occurs in a cultural context that is informed by legal constraints, social norms, and socio-political demands. Similarly, offender rehabilitation occurs in a context that is shaped by a wide range of pressures and involves practices that seek to recognise and understand the constellation of influences and mechanisms that impact on offending behaviour, as well as to apply therapeutic knowledge and processes that contribute to its prevention. The overarching rehabilitation journey often involves a number of phases that present opportunities for culturally responsive practices (e.g., risk assessment, treatment involvement, community reintegration). This chapter is a critical introduction to the importance of culture in offender rehabilitation practice and explores conceptual, design, ethical, and practice issues with programmes and practices that have been developed in Western settings. In addition to discussing the navigation of cultural differences when implementing Western-derived and validated practices, it is argued that a central issue of offender rehabilitation is to better prepare individuals for their world, rather than an imposed hypothetical one that is incommensurate with the realities of the person's reintegration pathway.